Recovery of Identity in Hidden Memory: A Gesture Life by Chang-Rae Lee - Park, Yoanna; Mustofa, Ali; Kurnia, Fabiola D. (NOBEL: Journal of Literature and Language Teaching, 2022)
This paper examines the novel A Gesture Life (1999), written by a Korean American writer, Chang-rae Lee, focusing on the theme of recovering a hidden identity. For this purpose, the persona theory of C.G. Jung was applied as a device for understanding the identity issue. A retired businessman Franklin Hata, born to Korean parents, is a man of multi-identity through adoption to a Japanese family and immigration to America, where he is reputed to be an ideal Asian immigrant. Psychologically suffering from conflict in his relationship with his adopted daughter, Sunny, he reflects on his past and encounters the traumatic memory that he has been holding deep in his unconscious. The findings show that Hata’s aim of assimilating into mainstream society urges him to erase his memory and conceal his identity behind his persona; his reconciliation with his memory helps him stand as a man free from the gesture.